0=-5n-2n-2n

Simple and best practice solution for 0=-5n-2n-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=-5n-2n-2n equation:


Simplifying
0 = -5n + -2n + -2n

Combine like terms: -5n + -2n = -7n
0 = -7n + -2n

Combine like terms: -7n + -2n = -9n
0 = -9n

Solving
0 = -9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '9n' to each side of the equation.
0 + 9n = -9n + 9n
Remove the zero:
9n = -9n + 9n

Combine like terms: -9n + 9n = 0
9n = 0

Divide each side by '9'.
n = 0

Simplifying
n = 0

See similar equations:

| (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 |

Equations solver categories